2011
DOI: 10.1007/s10096-011-1321-z
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus infections in children under 5 years of age hospitalized due to the acute viral gastroenteritis in northeastern Poland

Abstract: The primary aim of this study was to evaluate the frequency and seasonality of norovirus infection in hospitalized Polish children under 5 years of age, and a secondary aim was to compare the clinical severity of norovirus and rotavirus disease. The prospective surveillance study was carried out from July 2009 through June 2010. Stool samples from 242 children hospitalized due to acute viral gastroenteritis were tested for rotavirus group A and adenovirus with commercial immunochromatographic test and for noro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
19
3
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 21 publications
15
19
3
5
Order By: Relevance
“…Approximately the same rate was reported (2.1%) in a Polish study [3], but our rate is lower than that reported in France by Tran et al [36]. As reported in the present study and the French study [36], there was no significant correlation between the severity of gastroenteritis and combined infections.…”
Section: Discussionsupporting
confidence: 76%
“…Approximately the same rate was reported (2.1%) in a Polish study [3], but our rate is lower than that reported in France by Tran et al [36]. As reported in the present study and the French study [36], there was no significant correlation between the severity of gastroenteritis and combined infections.…”
Section: Discussionsupporting
confidence: 76%
“…The frequency of rotavirus infections in Poland varies from 20.4% to 48.9%, depending on the age and the season of the year, 6,19 and is similar to what is observed in other countries (18.7% -55%). 16,18,20 Although in our study rotaviruses can be responsible for ~1/3 cases of all hospitalizations for acute diarrhoea, it should be added that in 35% of Among the bacterial enteropathogens, toxigenic C. difficile strains were predominant agents in the studied population, found in 17% of the children with diarrhoea, regardless of previous antibiotic treatment.…”
Section: Discussionsupporting
confidence: 76%
“…An estimated catchment population accounts for approximately 8,200 children aged <5 years, representing about 50% of all children at this age in our region. 6 Acute diarrhea was defined as the passing of three or more loose or watery stools within a 24 h period and/or vomiting with or without fever. Inclusion criteria were as follows, age <5 years and written informed consent from the children's parents or legal guardians.…”
Section: Introductionmentioning
confidence: 99%
“…Acute gastroenteritis is a common disease, with high morbidity and mortality worldwide, especially in children. Norovirus (NoV) is recognized as the second most important etiological agent of nonbacterial diarrhea in children after Rotavirus [Patel et al, ; Mans et al, ; Kaplan et al, ; Nataraju et al, ; Oldak et al, ; Zeng et al, ]. A systematic review of reported literatures by Patel et al [] showed that NoV accounted for 12% (95% confidence interval [CI] 10–15%) of sporadic gastroenteritis cases among children <5 years worldwide.…”
Section: Introductionmentioning
confidence: 99%